Pengaruh Konsentrasi Asam Stearat dan Selulosa dari Limbah Padat Pengolahan Tapioka Terhadap Karakteristik Biokomposit Foam Tapioka dan Glukomanan - Ferdiansyah, Pupung; Harsojuwono, Bambang Admadi; Arnata, I Wayan (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 2 (2022)DO - 10.24843/JITPA.2022.v07.i02.p04, 2022)
Abstract This study aims to determine the effect of the concentration of stearic acid and cellulose from tapioca processing solid waste on the characteristics of tapioca foam biocomposite and glucomannan and to determine the optimal concentration of stearic acid and cellulose from tapioca processing solid waste so as to produce the best characteristics of tapioca foam and glucomannan biocomposite. This study used a randomized block design with two factors. Factor I is the concentration of stearic acid which consists of 3 levels (2% ; 4% ; 6%). Factor II is the concentration of maleic anhydride which consists of 3 levels (2.5%; 5%; 7.5%). The variables observed were tensile strength/breaking stress (tensile strength), density (mass density), tear resistance, compression set, thickness, swelling, and biodegradation time. The data obtained were analyzed for diversity (ANOVA) and continued with Duncan's test using Microsoft Excel 2016. The results showed that the concentration of stearic acid had a very significant effect on tensile strength, tear resistance, compressibility, swelling, biodegradation, but had no significant effect on density and thickness. The concentration of cellulose has a very significant effect on tensile strength, tear resistance, compressibility, swelling, biodegradation and has a significant effect on thickness, but has no significant effect on density. The interactions have a very significant effect on tensile strength, tear resistance, permanent compression, swelling, biodegradation, but have no significant effect on density and thickness. Concentration of 6% stearic acid and 5% cellulose produced the best foam biocomposite with tensile strength value of 0.69 N/cm2, tear resistance 0.49 N/cm2, density 0.20 g/ml, constant compression 7.61%, thickness 10 .27 mm, swelling 0.55%, and degradation time for 13.67 days. Keywords : Biocomposite foam, tapioca, glucomannan, stearic acid, cellulose.